1989
DOI: 10.1037/h0084230
|View full text |Cite
|
Sign up to set email alerts
|

Early interference in a priming task with brief masked targets.

Abstract: Priming effects were examined in two experiments using either a pronunciation or lexical decision task. The prime, cither a strong associate of the target, an unrelated word, or a neutral prime, was presented for 200 ms. After an SOA ol 200, 400, or 8(K) ms, a masked target was presented for 33.3, 50, or 66.7 ms. Attention was manipulated by varying the probability that prime and target would be strongly associated. Both experiments showed significant interference in the low attention condition and at the 200-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…For example, there are models with local representations for word nodes in which activity in a node is strongly affected by activity in other nodes (cf. Martindale, 1981; McClelland & Rumelhart, 1981; 4 McLeod & Walley, 1989; Rumelhart & McClelland, 1982; Walley & Weiden, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there are models with local representations for word nodes in which activity in a node is strongly affected by activity in other nodes (cf. Martindale, 1981; McClelland & Rumelhart, 1981; 4 McLeod & Walley, 1989; Rumelhart & McClelland, 1982; Walley & Weiden, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…This is because additional target strength would be necessary to overcome the contribution of the previous word to the response strength of the other potential responses. It is therefore not at all clear that a difference between magnitude of the relatedness effect spanning an intervening unrelated word and the magnitude of the relatedness effect spanning an intervening nonlinguistic stimulus demands a distributed account (see also McLeod & Walley, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This application of ACT* is rather complex in comparison with the Collins and Loftus (1975) model of automatic spreading activation, and it will be challenging to develop principles that can account for changes in the delay parameter and allocation of attention. Joordens and Besner (1992) suggested that disruption of priming by an intervening stimulus is not a critical result for local representation models because (a) the notion of automatic spreading activation as embodied in models such as those of Collins and Loftus (1975), Anderson (1983), andNeely (1991) are not widely held and (b) there are other variants of this class of model that assume inhibitory connections between word nodes, and these models should account for the obtained results (Martindale, 1981;McClelland & Rumelhart, 1981;McLeod & Walley, 1989;Walley & Weiden, 1973). With respect to the importance of the concept of automaticity in spreading activation, it should be noted that the lack of disruption by a small number of intervening items is a component of a number of current theories of semantic priming (e.g., McNamara, 1992aMcNamara, , 1992bMcNamara, , 1994 and is essential to modular theories of language processing in which intralexical priming is assumed to be responsible for sentence context effects in word identification (Seidenberg & Tanenhaus, 1986;Tanenhaus & Lucas, 1987).…”
Section: Spreading Activation With Local Representationmentioning
confidence: 99%
“…In contrast, normal s begin to show attentional, strategy-driven effects when the SOAs are longer than 400 ms; at these longer SOAs, the priming effect increases with the proportion of semantically related pairs in the list, and interference from unrelated primes is present (de Groot, 1984; den Heyer, Briand, & Dannenbring, 1983; Neely, 1977; but cf. McLeod & Walley, 1989). One method sometimes used to control for expectancy effects is continuous priming—subjects respond to both primes and targets with no explicit marking between them.…”
mentioning
confidence: 99%